An introduction to comparative legal models of criminal justice - Roberson, Cliff 1937-; Das, Dilip K. 1941- (CRC Press, 2008)
While in Plato's time there may have been some truth to his belief that there can only be one single justice, and one single law, such is not the case today. Criminal justice systems vary widely across the world in their approaches to the problem of crime. This book presents the theme that a country's legal model to a great extent determines the character of its police and corrections as well as its legal system. It examines these different systems and is a useful reference guide for all criminal justice professionals.
Keywords: Criminal justice, Administration of; Comparative law; Rechtssystem; Internationaler Vergleich; Strafrecht